2023
DOI: 10.2478/johh-2023-0009
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in aggregate characteristics of thermally heated water-repellent soil aggregates under laboratory conditions

Abstract: The heat generated during wildfires modifies soil characteristics, including soil water repellency (SWR) and the water stability of aggregates, which are known to be interrelated. SWR lowers the rate of water entry into aggregates, minimizing aggregate disruption and subsequent erosion. This study aimed to examine these aggregate characteristics (SWR, water stability of aggregates) of thermally heated water-repellent soil aggregates under laboratory conditions. Water-repellent aggregates were collected from Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Negri et al [36] observed an increase in WDPT with increasing heating temperatures in an interval from 50 • C to 200 • C and a dramatic drop to 0 for the heating temperature of 250 • C in Regosols and Cambisols. Perera et al [37] found that both the persistence and severity (estimated using the Molarity of an Ethanol Droplet test) of SWR of aggregates from sandy soil decreased with the heating temperature and all aggregates were wettable once exposed to 250 • C.…”
Section: Discussionmentioning
confidence: 99%
“…Negri et al [36] observed an increase in WDPT with increasing heating temperatures in an interval from 50 • C to 200 • C and a dramatic drop to 0 for the heating temperature of 250 • C in Regosols and Cambisols. Perera et al [37] found that both the persistence and severity (estimated using the Molarity of an Ethanol Droplet test) of SWR of aggregates from sandy soil decreased with the heating temperature and all aggregates were wettable once exposed to 250 • C.…”
Section: Discussionmentioning
confidence: 99%
“…The average value of three replicates was considered as the WDPT value of a particular sample. The measurement was terminated after 3600 s, and the penetration times exceeding 3600 s were considered as 3600 s. The SWR of samples can be categorized based on the WDPT values, as wettable (WDPT ≤ 1 s), non-repellent (WDPT = 1-5 s), slightly (WDPT = 5-60 s), strongly (WDPT = 60-600 s), severely (WDPT = 600-3600 s), and extremely water-repellent (WDPT = ≥3600 s) (Bisdom et al, 1993;Perera et al, 2023).…”
Section: Moisture-dependent Repellency Measurementmentioning
confidence: 99%